THE INFLUENCE OF VISUALIZATION STRATEGY ON READING COMPREHENSION ABILITY - Musdizal, Musdizal (JURNAL DIMENSI, 2019)
The objective of thisresearch was to know the effect of using Visualization Strategy in teaching recount text on reading comprehensionability at the second grade students of SMPN 4 Kerinci. Then, the type of the researchwas quasi experimental research. Besides, the population of the research was the second grade students of SMPN 4 Kerinci, it was 75 students. Moreover, the sample of this research consisted of 50 students from two classes. There were experiment class and control class. The analysis of data used t-test. The result of the research showedthat there was significance effect of using Visualization strategy toward studentsâ€™ reading comprehension of recount text. It could be seen of hypothesis was gotten the mean of control class was 60 and the standard deviation was 102 while the experimental class was 67,8 and standard deviation was 118,16. And after doing t-test, it was found that tobserve = 2,6 ttable = 1,68. It can be summarized that there was the significant effect of using visualization strategy in the studentsâ€™ reading comprehension achievement of recount text.Â